Going Bone Deep: Osseous Rosai–Dorfman Disease in an Adult with Recurrent, Culture-Negative Osteomyelitis - Dominick S. DeFelice; Megan L. Srinivas; Sara E. Wobker; Jonathan B. Parr (Case Reports in Infectious Diseases)
A patient presented for medical care on three separate occasions over the course of two years with recurrent right knee pain attributed to chronic osteomyelitis. Careful assessment revealed that his symptoms were caused by osseous Rosai–Dorfman disease. This case presents an alternative diagnostic possibility for culture-negative chronic osteomyelitis.